Effects of immunophilin inhibitors and non-immunosuppressive analogs on coronavirus replication in human infection models - Berthold, Emilia J.; Ma-Lauer, Yue; Chakraborty, Ashesh; von Brunn, Brigitte; Hilgendorff, Anne; Hatz, Rudolf; Behr, Jürgen; Hausch, Felix; Staab-Weijnitz, Claudia A.; von Brunn, Albrecht (Frontiers in Cellular and Infection Microbiology, 2022)
Rationale. Human coronaviruses (HCoV) seriously affect human health by causing respiratory disease ranging from common colds to severe acute respiratory disease. Immunophilins, including peptidyl-prolyl isomerases of the FK506-binding protein (FKBP) and the cyclophilin family, are promising targets for pharmaceutical inhibition of coronavirus replication, but cell-type specific effects have not been elucidated. FKBPs and cyclophilins bind the immunosuppressive drugs FK506 and cyclosporine A (CsA), respectively. Methods. Primary human bronchial epithelial cells (phBECs) were treated with CsA, Alisporivir (ALV), FK506 and FK506-derived non-immunosuppressive analogues and infected with HCoV-229E. RNA and protein were assessed by RT-qPCR and immunoblot analysis. Treatment with the same compounds was performed in hepatoma cells (Huh-7.5) infected with HCoV-229E expressing Renilla luciferase (HCoV-229E-RLuc) and the kidney cell line HEK293 transfected with a SARS-CoV-1 replicon expressing Renilla luciferase (SARS-CoV-1-RLuc), followed by quantification of luminescence as a measure of viral replication. Results. CsA and ALV robustly inhibited viral replication in all models: both compounds decreased HCoV-229E RNA in phBECs and reduced luminescence in HCoV-229E-RLuc-infected Huh7.5 and SARS-CoV-1-RLuc replicon-transfected HEK293. In contrast, FK506 showed inconsistent and less pronounced effects in phBECs, while strongly affecting coronavirus replication in Huh-7.5 and HEK293. Two non-immunosuppressive FK506 analogues had no antiviral effect in any of the infection models. Conclusion. The immunophilin inhibitors CsA and ALV display robust anti-coronaviral properties in multiple infection models, including phBECs reflecting a primary site of HCoV infection. In contrast, FK506 displayed cell-type specific effects, strongly affecting CoV replication in Huh7.5 and HEK293, but inconsistently and less pronounced in phBECs.